A Derridarean critique of Logocentrism as opposed to Textcentrism in John 1v1 - Hendricks, Gavin P. (Koers, 2014)
In Kelber’s hermeneutics of John, the notion of the pre-existence Logos is central. The Logos, in his reading, is prior to the realm of history and outside the reality of the narrative text. I have argued that the Logos in John can be seen as a leading case of logocentrism as coined by Derrida. The term ‘logocentrism’ refers to the Graeco-Christian or Johannine Platonic tradition according to which written language belongs to the realm of the imperfect whereas true knowledge pertains to the pre-existent, personified Logos. Derrida provides an uncompromising critique of logocentrism. He read Western theology and philosophy not in terms of a fading logocentrism and a rise of textcentrism, but rather in terms of the illusion of logocentrism. Derrida’s principle of distress is the referential paradigm of language. The linguistic sign is defined by the signifier and the signified. The signifier constitutes the visible marks committed to paper and the signified is the so-called meaning we attached to them. For Derrida, written language is generally seen as inferior whereas spoken language takes on transcendental significance and an ontological status to the referent of language. The Western tradition of philosophy and theology views writing as exterior whereas speech appears as innocent. Derrida’s logocentrism approach challenges the privileging of speech over writing in the referential system, accusing Western theology and philosophy of falsely enslaving the sign by establishing a transcendental signifier over against writing. In this article, these ideas of Derrida are applied by reading the Logos in the Johannine narrative from the perspective of orality and textuality.